MAKSIMALISASI LABA DALAM BISNIS SYARIAH: BATASAN SYARIAH TERHADAP PRAKTIK MONOPOLI, RIBA, DAN GHARAR - Putri, Putri Aulia; Azzahra Nurul A'isyah (Lobi, 2026)
This study examines the concept of profit maximization in Islamic business and the boundaries imposed by Sharia on economic practices such as monopoly, usury (riba), and excessive uncertainty (gharar), which often appear in modern business activities. Using a library research approach, this study explores classical and contemporary scholars’ perspectives on profit limits, ethical trading principles, and the impact of prohibited practices on market balance and social justice. The literature shows that Islam does not reject the pursuit of profit; however, it requires that gains be earned through fair, transparent, and non-exploitative mechanisms. The study also highlights current empirical conditions and proposes Sharia-based solutions to build ethical and equitable markets.